Menentukan Lokasi Gudang Eksternal PT Raja Roti Cemerlang Dengan Gravity Location Models - Ina Siti Hasanah; Neng Nita Silvia (Politeknik ATI Padang, 2023)
PT Raja Roti Cemerlang is a food industry that produces bread flour. PT Raja Roti Cemerlang plans to add a new warehouse to expand its reach to existing customers by minimizing distribution distance and shipping costs. This research provides an analysis using mathematical modeling for the problem of selecting the location of new facilities for the company. This model is used with the aim of providing recommendations for the location of candidate warehouse facilities that will be used as a new warehouse that is centralized to its consumers. This research uses a gravity location model that is implemented simply with Microsoft Excel software. This method is used based on its suitability with the identification of problems that the company has. In this research, the data needed to determine the best facility location in accordance with the gravity location method procedure is collected. The data collected is consumer-related data from the company PT Raja Roti Cemerlang such as location (latitude, longitude), number of requests, and distance data. The results of managerial analysis related to the old location and new location for facilities that will be used by the company show a new location with coordinates -6.178209493, 106.8433249 which is located in the Senen area, Central Jakarta City, Special Capital Region of Jakarta which has been projected by having a total difference in distance between the initial distribution location and the location of the external warehouse alternative 3 which is 198.37 km and the difference in shipping costs of Rp. 466,170.